Leaf trait responses to global change factors in terrestrial ecosystems - Hai, Xuying; Shangguan, Zhouping; Peng, Changhui; Deng, Lei (The Science of the total environment, 2023)
Global change influences plant growth by affecting plant morphology and physiology. However, the effects of global change factors vary based on the climate gradient. Here, we established a global database of leaf traits from 192 experiments on elevated CO2 concentrations (eCO2), drought, N deposition, and warming. The results showed that the leaf mass per area (LMA) significantly increased under eCO2 and drought conditions but decreased with N deposition, whereas eCO2 levels and drought conditions reduced stomatal conductance and increased and decreased photosynthetic rates, respectively. Leaf dark respiration (Rd) increased in response to global change, excluding N deposition. Leaf N concentrations declined with eCO2 but increased with N deposition. Leaf area increased with eCO2, N deposition, and warming but decreased with drought. Leaf thickness increased with eCO2 but decreased with warming. eCO2 and N deposition enhanced plant water-use efficiency (WUE), eCO2 and warming increased photosynthetic N-use efficiency (PNUE), while N fertilization reduced PNUE significantly. eCO2 produced a positive relationship between WUE and PNUE, which were limited under drought but increased in areas with high humidity and high temperature. Trade-offs were observed between WUE and PNUE under drought, N deposition, and warming. These findings suggest that the effects of global change factors on plants can be altered by complex environmental changes; moreover, diverse plant water and nutrient strategy responses can be interpreted against the background of their functional traits. [Display omitted] •Established a database of leaf traits from global change manipulation experiments•Plant physiology is more responsive to global change factors than morphology.•Effects of global change factors vary with climate gradients.•A positive relationship existed between WUE and PNUE under eCO2.•There were trade-offs between WUE and PNUE under drought, N deposition and warming.